The Expression of The PfEMP1-DBL2β Recombinant Protein of Plasmodium falciparum Isolated From Indonesia - Hasanah, Fathul Hidayatul; Sulistyaningsih, Erma; Sawitri, Widhi Dyah (Jurnal ILMU DASAR, 2020)
The binding of Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) to Intracellular Adhesion Molecule-1 (ICAM-1) is a major pathological mechanism in severe malaria including cerebral malaria. The binding is mediated by PfEMP1-DBL2β domain. The study aimed to explore there combinant protein of PfEMP1-DBL2β domain of P. falciparum isolated from Indonesia. DNA was isolated from a severe malaria patient. The DBL2β domain was amplified using Polymerase Chain Reaction (PCR) with specific primer and cloned into the pJET1 cloning vector. The DBL2β recombinant protein was constructed from DBL2β-pJET1 clone using pET-30a expression vector and expressed in Escherichia coli BL21-DE3. PCR colony and digestion of plasmid clones using restriction enzymes were conducted to confirm cloning result, and the expression of recombinant protein was analyzed using Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE). The expression of DBL2β-PfEMP1 domain is higher in pellet than in supernatant fraction. In conclusion, the DBL2β-PfEMP1 domain recombinant protein of P. falciparum isolated from Indonesia expressed as a ~66 kDa protein in full length. Keywords: DBL2β domain, Indonesia, PfEMP1, Plasmodium falciparum, recombinant protein.